Heart to Heart: The Power of Lyrical Bonding in Romantic Nationalism - Joep Leerssen (Interlitteraria)
In nineteenth-century nation-building, the textual genres investigated by researchers are usually long-distance, mediated ones, such as journalism and the novel. This article attempts to assess the function of a much more intimate literary genre, the lyrical, in that process. Lyricism was a central poetical element in Romanticism; its emotive, affect-centered mode was seen as specifically “immediate”, non-mediatized and deeply personal (and therefore non-political). How could this register aid the formation of self-defining national communities? The article suggests a special role for female poets and a privileged position of the lyrical in the interplay between print-disseminated literature and oral-performative literature, in shaping the nation as an “emotive community”.